Gaining from disorder: Making the case for antifragility in purchasing and supply chain management. Issue 3 (June 2021) - Nikookar, Ethan; Varsei, Mohsen; Wieland, Andreas
Abstract: The purchasing and supply chain management (P&SCM) discipline assumes that supply chains are fragile systems, hence taking a "negative" approach toward disorder. Building on Taleb's concept of antifragility—the ability to gain from disorder rather than avoiding it—, we challenge this traditional assumption. The COVID-19 pandemic has revealed that some companies were indeed able to gain from disorder, whereas some of those that focused too much on robustness and resilience lost ground. Building robust and resilient supply chains may no longer be enough to thrive in today's highly volatile business world. This article sparks a new debate by introducing antifragility to the P&SCM literature and provides new directions for future research. Highlights: Questions negative approaches to deal with disorder/disruption. Presents a positive alternative by introducing antifragility to the P&SCM literature. Defines antifragile supply chains as supply chains that gain from disorder/disruption.